การจัดการเรียนรู้ออนไลน์ด้วย Microsoft Teams Application ของมหาวิทยาลัยมหามกุฏราชวิทยาลัย วิทยาเขตศรีล้านช้าง - บุญหนัก, สุพรรณี; โพดาพล, จักรกฤษณ์ (วารสารศรีล้านช้างปริทรรศน์; Vol 7 No 1 (2021): วารสารศรีล้านช้างปริทรรศน์ ปีที่ 7 ฉบับที่ 1 (มกราคม - มิถุนายน 2564), 2021)
บทความนี้มีวัตถุประสงค์เพื่ออธิบายเกี่ยวกับการจัดการเรียนรู้ออนไลน์ด้วย Microsoft Teams Application ของมหาวิทยาลัยมหามกุฏราชวิทยาลัย วิทยาเขตศรีล้านช้าง ในช่วงสถานการณ์การแพร่ระบาดของไวรัสโคโรน่า 2019 หรือ COVID – 19 ที่ทำให้การเรียนการสอนมีประสิทธิภาพ ส่งผลต่อการเรียนการสอนที่มีคุณภาพของผู้เรียน ในกระบวนการพัฒนาการเรียนการสอนนี้ได้มีขั้นตอนต่าง ๆ รวมทั้งการจัดองค์กรในรูปคณะกรรมการชุดต่าง ๆ ขึ้นเพื่อช่วยขับเคลื่อนการเรียนการสอนออนไลน์ให้ประสบความสำเร็จ             The objective of the academic article was to explain the online learning management with Microsoft Teams Application in Mahamakut Buddhist University, Srilanchang Campus, during the coronavirus outbreak in 2019 (COVID-19). As a result, the learning process was found effective and the quality of students was also found higher. In addition, the process of learning development consisted of several interesting procedures, including the committee-based organizational administration, and it contributed to drive successful online teaching and learning in the educational institutions.